E-service quality of online shopping website: customer satisfaction in Lazada - Mohd Fudzi, Fatin Syahirah (2019)
Customers are very important to online vendors; therefore, customer satisfactions become their main focus. For organisations and researchers alike, satisfaction of customer has been a topic of foremost concern. Recently, online vendors are required to offer more services on their websites. In conjunction with that, quality of service has become an important aspect of customer satisfaction. Studies in the literature have shown that the quality of service is linked to customer satisfaction, including through online services. In the context of online services, some researchers used measurements of e-service quality to assess the quality of service. However, there are limited research on the relationship between customer satisfaction and eservice quality dimensions of the online shopping website. Therefore, the main objective of this study is to examine the relationship between e-SERVQUAL dimensions and customer satisfaction on the online shopping website. The survey of 206 customers of postgraduate students in Universiti Utara Malaysia were used to test the research model and to examine their satisfaction levels of online shopping using the e-SERVQUAL model. SPSS software was used for data analysis, in which correlation test and multiple regression were used to test the hypotheses. Findings showed that the dimensions of web site design, reliability, personalization and trust affect the satisfaction of customers on online shopping website. However, responsiveness is insignificantly related to customer satisfaction. The results recommended that online shopping website providers need to focus on significant elements of the service quality dimensions in order to enhance customers’ satisfaction.